Zmiana paradygmatu zarządzania strategicznego - zarys koncepcji - Witek-Crabb, Anna (Change of the Strategic Management Paradigm - Concept Outline, 2006)
The discipline of strategic management is undergoing evolution. The need for a new paradigm in strategic management appeared as a response to the changes in business environment, which in turn resulted in the necessity to reformulate the concept of a firm, a strategist and a strategy. The new paradigm in strategic management builds a shift from thinking about the business environment as stable to thinking about it as chaotic. From hierarchic firm with linear organizational structure to an open system company with flat and flexible structure. From a technocratic and finance-oriented strategist to a socially sensitive, versatile and professional strategist. From a strategy defined as a rigid goal oriented plan to a strategy as an emergent flexible concept, coherent with the company's dominant logic.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 377-386